2003
DOI: 10.1042/bj20030806
|View full text |Cite
|
Sign up to set email alerts
|

A novel antimicrobial protein isolated from potato (Solanum tuberosum) shares homology with an acid phosphatase

Abstract: The nucleotide and amino acids sequences for AP(1) will appear in the GenBank(R) and NCBI databases under accession number AY297449. A novel antimicrobial protein (AP(1)) was purified from leaves of the potato ( Solanum tuberosum, variety MS-42.3) with a procedure involving ammonium sulphate fractionation, molecular sieve chromatography with Sephacryl S-200 and hydrophobic chromatography with Butyl-Sepharose using a FPLC system. The inhibition spectrum investigation showed that AP(1) had good inhibition activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Wisely, combined with biotechnology advancement, plant-derived natural products have become a major trend in the development of modern pesticides. Up to now, it has been demonstrated that botanical antimicrobial substances from various plants (Gramineae, Labiatae, Apocynaceae, Rutaceae, Liliaceae and Magnoliaceae) [10,11,12,13], including secondary metabolites, have highly efficient sources of antimicrobial activity against agricultural phytopathogens [14,15,16,17] (Table 1). A great number of plant essential oils have been tested for their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Wisely, combined with biotechnology advancement, plant-derived natural products have become a major trend in the development of modern pesticides. Up to now, it has been demonstrated that botanical antimicrobial substances from various plants (Gramineae, Labiatae, Apocynaceae, Rutaceae, Liliaceae and Magnoliaceae) [10,11,12,13], including secondary metabolites, have highly efficient sources of antimicrobial activity against agricultural phytopathogens [14,15,16,17] (Table 1). A great number of plant essential oils have been tested for their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…지난 10여 년간 QTL (quantitative trait loci)과 저항성 유전자를 분리하고 병방어 관련 유전자를 감자에 옮기기 위한 많은 노력이 있었다. 하지만 R gene인 AP1 gene [9], chitinase 나 defensin 같은 외래 유전자를 가지는 형질전환 감자, snakin-1과 snakin-2 같은 감자 유래 유전자 등 극히 적은 양의 유전자가 Rs에 대해 저항성이 증가한다고 보고되고 있다 [2]. 몇몇의 유전자가 클로닝되고 특성이 밝혀졌지만 감자와 Rs의 (Fig.…”
Section: 서 론unclassified
“…It has been shown in certain studies that plants protect themselves against microbial pathogens by various defense responses including production of antimicrobial peptides (AMPs), secondary metabolites, lytic enzymes and membrane-interacting proteins (Feng et al, 2003).…”
Section: Issn: 2319-7706 Volume 6 Number 8 (2017) Pp 1523-1533mentioning
confidence: 99%